Association Between Periodontitis and Low-Grade Albuminuria in Non-Diabetic Adults - Seok Hui Kang; Jong Won Park; Kyu Hyang Cho; Jun-Young Do (Karger Publishers, 2017)
Background/Aims: The objective of the present study was to evaluate the clinical association between periodontitis and a high urinary albumin/creatinine ratio (UACR) in individuals without diabetes mellitus. Methods: Data from the Korean National Health and Nutrition Examination Survey were used for this analysis. A high UACR was defined as UACR≥3.9 mg/g for men and UACR≥7.5 mg/g for women. The WHO community periodontal index (CPI) was used to define periodontitis and assess its severity. Results: The numbers of participants without and with periodontitis were 3,046 and 8,571, respectively. The UACR values were higher in participants with periodontitis than in those without periodontitis. Logistic regression showed that the OR for a high UACR with the presence of periodontitis was 1.14 (P=0.044) on multivariate analysis. CPI score was positively associated with UACR. Conclusions: Periodontitis was associated with UACR in the non-diabetic participants in this study. Therefore, participants with periodontitis should be closely monitored for UACR, which can function as an early marker for renal injury.